2017
DOI: 10.1103/physrevapplied.7.034035
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transitions, Semiconductor-Metal Transitions, and Fragilities in GeVTe ( V=As , Sb) Liquid Alloys: The Difference One Element Can Make

Abstract: Glass transition temperatures (T g ) and liquid fragilities are measured along a line of constant Ge content in the system Ge-As-Te, and contrasted with the lack of glass-forming ability in the twin system Ge-Sb-Te at the same Ge content. The one composition established as free of crystal contamination in the latter system shows a behavior opposite to that of more covalent system.Comparison of T g vs bond density in the three systems Ge-As-chalcogen differing in chalcogen i.e. S, Se, or Te, shows that as the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 71 publications
2
26
0
Order By: Relevance
“…Figure A shows the transition from semiconductor to metallic conductivity in Ge 15 Te 85 and Se 30 Te 70 melts. This behavior is representative of a large number of chalogenide melts as demonstrated long ago by Alekseev et al and recently discussed in relation to the M‐SC transition in PCMs by the present authors . The activation energy for conductivity E a is plotted in Figure B and exhibits a clear maximum for both melts.…”
Section: Metal‐to‐semiconductor Transitionssupporting
confidence: 82%
See 4 more Smart Citations
“…Figure A shows the transition from semiconductor to metallic conductivity in Ge 15 Te 85 and Se 30 Te 70 melts. This behavior is representative of a large number of chalogenide melts as demonstrated long ago by Alekseev et al and recently discussed in relation to the M‐SC transition in PCMs by the present authors . The activation energy for conductivity E a is plotted in Figure B and exhibits a clear maximum for both melts.…”
Section: Metal‐to‐semiconductor Transitionssupporting
confidence: 82%
“…On the other end, the high kinetic factor of fragile systems is disadvantageous in the glassy state as it may lead to crystallization of the amorphous bit at ambient temperature and loss of stored data. It was recently reported that this conundrum can be solved in PCMs such as AIST, Ge 15 Sb 85 or Ge 2 Sb 2 Te 5 where a sharp transition from fragile to strong occurs upon cooling, thereby providing the benefit of fast kinetics at high temperature and stabilization of the amorphous phase at low temperature . The structural origin of these L‐L transitions was characterized by employing femtosecond x‐ray diffraction to observe the change in local atomic environment before crystallization occurred on the nanosecond time scale.…”
Section: Implications To Memory Technologymentioning
confidence: 99%
See 3 more Smart Citations